Fa’aliyatu Istikhdậmi Tharîqah al-Istijậbah al-Jasadiyah al-Kậmilah bi Wasîlati Bithậqah al-Falash Litarqiyati Itsqậni al-Mufradật lada at-Talậmizi fi Madrasati Nûrul Imận al-Mutawassitah al-Islamiyah Indragiri Hilir/ فعالية استخدام طريقة الاستجابة الجسدية الكاملة بوسيلة بطاقة الفلاش لترقية إتقان المفردات لدى التلاميذ في مدرسة نور الإيمان المتوسطة الإسلامية اندراجيري هيلير - anggun sari, yola; ahmad, amrizal (Al-Manar, 2024)
It was experimental research with pretest and posttest, and it aimed at finding out the effectiveness of using Total Physical Response method with Flash Card media in increasing student vocabulary mastery at Islamic Junior High School of Nurul Iman Indragiri Hilir. The formulation of the problem in this research was "was Total Physical Response method with Flash Card media effective in increasing student vocabulary mastery at Islamic Junior High School of Nurul Iman Indragiri Hilir?". All students at Islamic Junior High School of Nurul Iman Indragiri Hilir were the population of this research, and the samples were the eighth-grade students of class A as the experimental group and the students of class B as the control group. The subjects were all students at Islamic Junior High School of Nurul Iman Indragiri Hilir. The object was the effectiveness of using Total Physical Response method with Flash Card media in increasing student vocabulary mastery at Islamic Junior High School of Nurul Iman Indragiri Hilir. Observation, test, and documentation were the instruments of collecting data. Based on data analysis, it could be concluded that Total Physical Response method with Flash Card media was effective in increasing student vocabulary mastery at Islamic Junior High School of Nurul Iman Indragiri Hilir. It could be proven with the score of tobserved 11.088 higher than table 2.406 at 1% significant level and 1.677 at 5% significant level, so Ha was accepted and Ho was rejected. In the observation table, the score was 96%, and it was very good (Jayyid Jiddan) because it was in the significant level of 86%-100%. With these data, the use of Total Physical Response method with Flash Card media was effective in increasing student vocabulary mastery at Islamic Junior High School of Nurul Iman Indragiri Hilir.